PENDEKATAN DESAIN PONDASI JALAN DI JALUR PANTURA - Rahadian, Hedy; ., Hendarto; Augustine, Julia (Jurnal HPJI, 2016)
Abstract Pantura Jawa Road, located in the corridor Javas north coast, is a national road which is very important in supporting economic growth in Indonesia, especially in Java economic growth. The road is located in the alluvial deposits in the category of soft soil that is